Unstable State of the [alpha]-Ti Crystal Lattice in the Surface Layers of Titanium Alloys Samples Treated by a Low-Energy High-Current Pulsed Electron Beam; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Perevalova O. B. (2018, 2018)
Title screen